PENGARUH TERAPI AKUPUNTUR TERHADAP PENINGKATAN KEKUATAN OTOT EXTERMITAS PADA PASIEN STROKE DI KLINIK ZEIN HOLISTIK THERAPY MAKASSAR - Fitriani Fitriani; Fatma Jama; Samsualam; Eliati Paturungi (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2025)
Stroke is one of the leading causes of disability, clinically manifested by muscle weakness, spasticity, and mobility disorders. Acupuncture therapy is a complementary treatment proven to improve blood circulation, reduce spasticity, and stimulate neuroplasticity, thereby potentially enhancing muscle strength in the extremities of stroke patients. Methods: This study employed a case study design involving stroke patients with muscle weakness in the extremities. Data were collected through observation of muscle strength using the Manual Muscle Testing (MMT) scale, assessment of mobility, and fall risk evaluation using the Morse Fall Scale, conducted before and after acupuncture intervention. Results:The intervention involved regular acupuncture therapy at specific points—Baihui(GV20), Taichong (LR3), Shenmai (BL6), Ququan (LR8), Huoxi (SI3), and Zhaohai (KI6)—which showed an improvement in lower extremity muscle strength fromgrade 4 to 5 on the MMT scale, an increase in range of motion (ROM), andenhanced ambulation ability. The fall risk category decreased from high (score 60) to low (score 25) after several sessions of acupuncture therapy. Conclusion: Acupuncture therapy has a positive effect on improving muscle strength in the extremities and reducing fall risk among stroke patients. It can be considered an effective complementary therapy in stroke rehabilitation to supportphysiotherapy and improve patients’ quality of life.